Coating method for electrolytic cell assembly
By using a platinum cationic acid solution and a reducing agent to form a platinum metal coating on the electrolytic cell assembly, the problems of high cost and high temperature requirements in the prior art are solved, and a low-cost and high-efficiency coating process suitable for large-scale manufacturing is achieved.
Patent Information
- Application Number
- CN202380062798.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-01
- Filing Date
- 2023-08-31
- Publication Date
- 2025-04-22
AI Technical Summary
The prior art has problems of high cost, complex operation and high temperature requirements when coating electrolytic cell components, and it is difficult to apply in large-scale production.
The platinum cationic acid solution is applied to the titanium module and the platinum cation is reduced using a reducing agent to form a platinum metal coating. The process can be implemented at low temperatures and is suitable for high-volume manufacturing without causing metal oxidation of the components.
It achieves the reduction of production costs, simplifies operating procedures, and avoids the additional costs of high-temperature treatment, and is suitable for large-scale production.
Smart Images

Figure CN119866392A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to polymer electrolyte membrane water electrolyzers (also known as electrochemical hydrogen generators) and, more particularly, to a method of coating components of such electrolyzers with platinum. Background Art
[0002] A polymer electrolyte membrane (PEM) water electrolyzer is an electrochemical device that decomposes water into hydrogen and oxygen. The hydrogen produced by the device provides a clean energy fuel source for hydrogen fuel cells. A PEM water electrolyzer includes a cathode, an anode, and a polymer electrolyte. Other components include bipolar plates, porous transport layers, and flow disruptors, and are typically made of titanium. Titanium is a preferred metal over iron-based and nickel-based materials that are susceptible to degradation.
[0003] PEM electrolysis has advantages over other types of electrolysis due to its high efficiency, high purity hydrogen output, and ability to produce hydrogen under pressure. However, its efficiency is limited by the internal resistance of the cell. In the early stages of operation, the membrane is the main limiting factor. However, over time, the cell voltage begins to drop. This is mainly due to the increase in contact resistance within the cell, which is ultimately due to the formation (thickening) of a titanium dioxide layer on the surface of the titanium component. When the thickness of the titanium dioxide layer exceeds the tunneling distance of electrons (1.23nm), the operating voltage rises exponentially, leading to catastrophic failure of the cell. This phenomenon usually occurs after about 5,000 to 10,000 hours of operation, but it may occur earlier or later, depending on other factors such as operating conditions and the construction materials of the power plant auxiliary equipment.
[0004] To solve this problem, a precious metal such as gold or a platinum group metal (platinum, iridium, palladium, rhodium or ruthenium, etc.) is usually coated on the component. Since the main function of the coating is to improve the contact resistance between metals and between metals and catalysts, it is not necessary to continuously cover the component.
[0005] Two common methods of coating titanium components are plating and physical (or chemical) vapor deposition.
[0006] Plating includes electroplating and chemical plating, both of which involve immersing the component in a solution of metal ions and causing the metal ions to undergo a reduction reaction on the surface of the component to form a metal coating. Electroplating uses an electric current to reduce the metal ions. There is a disadvantage to this process: in order to plate large component parts in a production environment, the plating tank (containing the plating solution) must be large enough to accommodate the entire component and must contain a correspondingly large amount of precious metal. Therefore, the plating solution is an expensive asset for the company, which leads to high production costs.
[0007] Electroless plating forms a metal coating by autocatalytic chemical reduction of metal cations, where the metal itself acts as a catalytic reducing agent. However, the method is not suitable for coating electrolytic cell components during production because the time required for the autocatalytic process to complete is too long.
[0008] Other electroless plating methods include thermal decomposition and powder sintering, both of which require high temperatures (e.g., in excess of about 300°C). A metal salt solution containing the electrode active coating material is first applied and, after drying, is heat treated in air at a temperature of, for example, 350°C to 550°C. Examples of platinum metal salts used in the process include chloroplatinic acid and dinitrodiammine platinum. One disadvantage of using the process is that the high temperatures required result in high operating costs, which limits the use of the process in mass production processes.
[0009] Vapor deposition also has disadvantages, namely that it requires the use of expensive equipment and high vacuum technology, which is difficult to apply in large-scale production.
[0010] Therefore, it is necessary to provide a coating method for electrolytic cell components to solve the above problems at least to some extent. Summary of the invention
[0011] According to the present invention, there is provided a method for coating an electrolytic cell component, wherein the component comprises titanium, the method comprising: applying an acidic solution of platinum cations to at least a portion of the component, and The applied platinum cations are reduced using a reducing agent to form a layer of platinum metal on the component.
[0012] Compared with existing coating methods, the method of the present invention is low-cost and suitable for mass production processes. The method can be implemented at low temperatures (eg, below 350° C.) and does not cause metal oxidation of the component.
[0013] The method may further include at least partially drying the applied platinum cation acidic solution. The temperature during drying may range from about 0°C to 200°C, about 25°C to 175°C, about 50°C to 150°C, about 75°C to 125°C, about 80°C to 100°C, about 90°C to 95°C, or less than about 350°C.
[0014] The temperature of the drying step is significantly lower than the temperatures used in the prior art thermal decomposition and powder sintering processes. This provides a process that is easier to operate and reduces operating costs.
[0015] The platinum cation acidic solution is applied to the component in an amount sufficient to provide approximately 0.01 mg / cm2 of platinum cation acidic solution on the component. 2 Up to 2.5 mg / cm 2 The loading range is comparable to the catalyst loading of conventional commercial components.
[0016] The components may be selected from the group consisting of one or more of: a cathode chamber or region, an anode chamber or region, a bipolar plate, a flow disruptor, and a porous transport layer.
[0017] The platinum cation acidic solution may be applied to the component by one or more methods selected from the group consisting of: brushing, dipping, spraying, and combinations thereof. The coating method ensures that platinum cations are uniformly coated on the component or a target portion thereof as desired.
[0018] The applied platinum cations may undergo a reduction reaction by contacting with a reducing agent. The contacting may include: brushing the applied platinum cations with a solution containing the reducing agent; immersing the component in a solution containing the reducing agent; spraying the component with a solution containing the reducing agent; or a combination thereof. The contacting may preferably include immersing the component in a solution containing the reducing agent. These contacting methods can achieve maximum reduction of platinum cations, thereby forming a uniform platinum metal coating on the component.
[0019] The method may further include at least partially drying the component after the platinum cations are reduced. For example, the drying may be performed after the component is immersed in a solution of the reducing agent. The temperature during drying may range from about 0°C to 200°C, about 25°C to 175°C, about 50°C to 150°C, about 75°C to 125°C, about 80°C to 100°C, about 90°C to 95°C, or less than about 350°C.
[0020] The drying process removes solvent in which the reducing agent may be present and can accelerate the reduction reaction by concentrating the reducing agent in contact with the platinum cations.
[0021] The platinum cation acidic solution may include about 1 wt % to 20 wt %, about 5 wt % to 15 wt %, or about 10 wt % of hydrochloric acid. The hydrochloric acid maintains the platinum cations in a charged state and limits the occurrence of side reactions.
[0022] The platinum cation acidic solution may include a platinum halide, and is preferably selected from one or more of the following: platinum chloride, platinum bromide and / or platinum fluoride. The platinum halide may include platinum chloride, and the platinum chloride may be selected from platinum tetrachloride, chloroplatinic acid (H2PtCl6) and platinum dichloride.
[0023] The reducing agent may include a hydride reducing agent, a phosphine reducing agent and / or a borane reducing agent. The hydride reducing agent may be selected from sodium borohydride and / or sodium cyanoborohydride. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In the attached picture:
[0025] Figure 1 Graph showing the difference in interfacial contact resistance between a titanium component coated according to the method of the present invention and subjected to accelerated corrosion testing and an uncoated titanium component. DETAILED DESCRIPTION
[0026] As used herein and in the appended claims, unless the context requires otherwise, “comprise” or variations such as “comprises”, “comprising”, etc., will be understood to imply the inclusion of a stated element or group of elements but not the exclusion of any other elements or groups of elements.
[0027] With respect to the ingredients of a component, the term "mainly comprising" will be understood to mean that the component contains the specified ingredients, but may also contain small amounts (i.e., less than 5wt%, and preferably less than 1wt%) of other ingredients or additives without significantly changing the chemical or physical properties of the component.
[0028] As used herein, the term "about" in relation to a stated quantity means that the stated quantity may vary within a range of ±5%. For example, about 90 wt% means 90 ± 5 wt%, about 0.1 wt% means 0.1 ± 0.005 wt%, and about 80°C means 80 ± 4°C. When used to express a range, the word "about" applies to all values within the range.
[0029] As used herein, the term "reducing agent" (also referred to as a reducing substance or reducing agent) refers to a chemical substance that participates in a redox reaction by reducing another chemical substance. It provides at least one electron and is oxidized in the process. Examples of reducing agents include hydrides, such as metal hydrides (NaH, LiH, CaH2, LiAlH4, and red aluminum (Red-Al), etc.) and borohydrides (NaBH4, NaBH3CN, and LiBH4, etc.), borane, and phosphine (triphenylphosphine, etc.). The reducing agent mentioned in the present disclosure may include one or more chemical substances selected from these groups.
[0030] The present disclosure provides a coating method for an electrolytic cell component. The coating minimizes interfacial contact resistance by preventing the formation of titanium dioxide during operation of the electrolytic cell, thereby maintaining the efficiency of the electrolytic cell and extending its service life. The method includes applying an acidic solution of platinum cations to at least a portion of the component and reducing the applied platinum cations using a reducing agent to form a layer of platinum metal on the component. The resulting coating can be continuous, discontinuous, or a combination thereof. The degree of continuity of the coating can be determined by electron microscopy, such as a transmission electron microscope (TEM), a scanning electron microscope (SEM), or a scanning transmission electron microscope (STEM), but any suitable method can also be used.
[0031] The platinum cation acidic solution can be applied to the component by one or more coating methods selected from the group consisting of: brushing, dipping, spraying, and combinations thereof. If the method of the present invention is implemented in multiple cycles, more than one coating method can be used. For example, the first cycle can include dipping and the second cycle can include spraying. Using a combination of different methods can achieve the desired platinum loading, because different methods will generally apply different volumes of solution to the component surface.
[0032] The platinum cation acidic solution may contain 0.1M to 5M, 0.5M to 2M, 0.5M to 1.5M or about 1M of an acid, or about 1wt% to 20wt%, about 5wt% to 15wt% or about 10wt% of an acid. The acid may be selected from hydrochloric acid, H2SO4, HNO3 and CH3COOH, and is preferably hydrochloric acid.
[0033] The platinum cation may comprise a platinum halide or dinitrosodiammine platinum. The platinum halide may preferably be selected from one or more of: platinum chloride, platinum bromide and / or platinum fluoride. Platinum chloride is particularly preferred because chloride ions are also present in the preferred acid (i.e., hydrochloric acid). The platinum chloride may be selected from: platinum tetrachloride, chloroplatinic acid (HPtCl) and platinum dichloride. In a preferred embodiment, the platinum cation comprises chloroplatinic acid.
[0034] The platinum cation acidic solution is applied to the component in an amount sufficient to provide approximately 0.01 mg / cm2 of platinum cation acidic solution on the component. 2 Up to 2.5 mg / cm 2 , about 0.01mg / cm 2 Up to 2.0mg / cm 2 , about 1.0mg / cm 2 Up to 2.0mg / cm 2 , about 1.25mg / cm 2 Up to 1.5 mg / cm 2, about 0.1mg / cm 2 Up to 2.0mg / cm 2 , about 0.01mg / cm 2 Up to 1.5 mg / cm 2 or about 0.01 mg / cm 2 Up to 1mg / cm 2 The method can be implemented iteratively or multiple times (i.e., divided into multiple cycles) to achieve the desired platinum loading. For example, the method can be implemented 2 to 50 times, 2 to 20 times, 2 to 15 times, 2 to 10 times, or 2 to 5 times.
[0035] The method may also include at least partially drying the component after applying the solution. The acidic solution is typically an aqueous solution and the drying step removes substantially all of the water, leaving a residue of the platinum cations on the surface of the component. The drying step may be performed at a temperature ranging from about 0°C to 200°C, about 25°C to 175°C, about 50°C to 150°C, about 75°C to 125°C, about 80°C to 100°C, about 90°C to 95°C, or less than about 350°C, less than about 300°C, less than about 250°C, less than about 200°C, less than about 150°C, less than about 100°C, or less than about 95°C. A gas, such as air, may be blown across the surface of the component to accelerate drying. Optionally, the gas is heated.
[0036] The component may be selected from the group consisting of one or more of: a cathode chamber or cathode region, an anode chamber or anode region, a bipolar plate, a spoiler, and a porous transport layer. For example, the component may be a bipolar plate or a porous transport layer. The component may be made of a material comprising titanium. The component may mainly comprise titanium before coating. For example, the component may be a titanium component. The component may comprise at least 80 wt%, at least 85 wt%, at least 90 wt%, at least 95 wt%, at least 96 wt%, at least 97 wt%, at least 98 wt%, at least 99 wt%, 100 wt% titanium, or a range between any two values therein.
[0037] The reducing agent is a chemical reducing agent, which may include a hydride reducing agent, a borane reducing agent and / or a phosphine reducing agent. Preferably, the reducing agent includes a hydride, more preferably a borohydride, or even more preferably NaBH4 and / or NaBH3CN. The reducing agent may be in the form of a solution, such as an aqueous solution.
[0038] The reducing step comprises contacting the applied platinum cations with the reducing agent. The contacting may comprise: brushing the applied platinum cations with a solution comprising the reducing agent; immersing the component in a solution comprising the reducing agent; spraying the component with a solution comprising the reducing agent; or a combination thereof. The contacting may preferably comprise immersing the component in a solution comprising the reducing agent. The component may be washed to remove any salts or impurities remaining after reduction.
[0039] The method may also include at least partially drying the component. When the reducing agent is present in the form of a solution, it is typically present in the form of an aqueous solution, and the drying step removes any moisture that may be present on the surface of the component. The temperature range when performing the drying step can be about 0°C to 200°C, about 25°C to 175°C, about 50°C to 150°C, about 75°C to 125°C, about 80°C to 100°C, about 90°C to 95°C, or less than about 350°C, less than about 300°C, less than about 250°C, less than about 200°C, less than about 150°C, less than about 100°C, or less than about 95°C. A gas (e.g., air) may be blown over the surface of the component to accelerate drying. Optionally, the gas is heated. Example
[0040] First, a titanium sheet cut and processed into a certain size (20cm x 20cm) was cleaned with water, and then placed in an ultrasonic bath filled with acetone for about 10 minutes of decontamination. After drying, the sheet was rinsed 3 times with deionized water. 10g of chloroplatinic acid (H2PtCl6) was dissolved in 1M hydrochloric acid solution to prepare a coating solution. The solution was applied to the previously prepared titanium plate by brushing to achieve 12.5g / m 2 Up to 15.0g / m 2 The coated portion was dried at 90°C and reweighed to ensure that the H2PtCl6 loading reached 1.25 g / m 2 Up to 1.5g / m 2 The dried part was then immediately immersed in a 1 M Na2BH4 solution for 2 seconds. The platinum salt was reduced to platinum on the titanium surface as evidenced by the appearance of hydrogen bubbles on the surface of the part.
[0041] In order to simulate the effect of accelerated corrosion in an electrolytic cell, the titanium component was placed in a solution containing 1 mg / l NaF (2.4 x 10 -5 M) in an aqueous solution and allowed to stand for 1 hour. An uncoated (decontaminated) titanium part was placed in the same solution and allowed to stand for the same time. After 1 hour, both parts were rinsed with deionized water and dried at 90°C.
[0042] By placing a 1cm 2 The gold-plated copper disc is subjected to 1.96N / cm 2 The contact resistance of the parts was measured by applying a pressure of 1A between the copper disk and the titanium part and using a calibrated digital voltmeter to measure the voltage between the copper disk and the titanium. According to Ohm's law, the voltage is directly converted to Ω.cm 2 The contact resistance of the coated parts is in the range of 1mΩ.cm 2 Up to 6mΩ.cm 2 , while the contact resistance of the uncoated parts exceeds 100mΩ.cm 2 The results are shown in Tables 1 and Figure 1 . Table 1
Claims
1. A coating method for an electrolytic cell component, characterized in that: The component comprises titanium, and the method comprises: applying an acidic solution of platinum cations to at least a portion of the component, and The applied platinum cations are reduced using a reducing agent to form a layer of platinum metal on the component.
2. The method according to claim 1, characterized in that Also included is at least partially drying the applied platinum cation acidic solution.
3. The method according to claim 2, characterized in that The temperature during drying ranges from 0°C to 200°C, about 25°C to 175°C, about 50°C to 150°C, about 75°C to 125°C, about 80°C to 100°C, about 90°C to 95°C, or less than about 350°C.
4. The method according to any one of the preceding claims, characterized in that The platinum cation acidic solution is applied to the component in an amount sufficient to provide 0.01 mg / cm 2 Up to 2.5 mg / cm 2 of platinum loading.
5. The method according to any one of the preceding claims, characterized in that The components are selected from one or more of the following: a cathode chamber or cathode region, an anode chamber or anode region, a spoiler, and a bipolar plate.
6. The method according to any one of the preceding claims, characterized in that The component is a titanium component.
7. The method according to any one of the preceding claims, characterized in that The platinum cation acidic solution is applied to the component by a method selected from the group consisting of: brushing, dipping, spraying, and combinations thereof.
8. The method according to any one of the preceding claims, characterized in that The reducing comprises: brushing the applied platinum cations with a solution containing the reducing agent; immersing the component in a solution containing the reducing agent; spraying the component with a solution containing the reducing agent; or a combination thereof.
9. The method according to any one of the preceding claims, characterized in that The reducing comprises immersing the assembly in a solution comprising the reducing agent.
10. The method according to any one of the preceding claims, characterized in that Also included is drying the assembly after the contacting step.
11. The method according to any one of the preceding claims, characterized in that The platinum cation acidic solution includes 1 wt % to 20 wt %, 5 wt % to 15 wt % or 10 wt % of hydrochloric acid.
12. The method according to any one of the preceding claims, characterized in that The platinum cation acidic solution comprises a platinum halide, and is preferably selected from one or more of the following: platinum chloride, platinum bromide and / or platinum fluoride.
13. The method according to claim 12, characterized in that The platinum halide comprises platinum chloride, and the platinum chloride is selected from the group consisting of platinum tetrachloride, chloroplatinic acid (H2PtCl6) and platinum dichloride.
14. The method according to any one of the preceding claims, characterized in that The reducing agent includes a hydride reducing agent, a phosphine reducing agent and / or a borane reducing agent.
15. The method according to claim 14, characterized in that The hydride reducing agent is selected from sodium borohydride and / or sodium cyanoborohydride.